2022
DOI: 10.1002/anie.202210207
|View full text |Cite
|
Sign up to set email alerts
|

Diastereo‐ and Enantioselective Synthesis of Bisbenzannulated Spiroketals and Spiroaminals by Ir/Ag/Acid Ternary Catalysis

Abstract: We reported herein an iridium/silver/acid ternary catalytic system to access bisbenzannulated [6,6]-spiroketals in high efficiency with generally high diastereo-and enantioselectivities (up to > 20 : 1 dr, > 99 % ee). In this procedure, readily available o-alkynylacetophenones undergo cycloisomerization to generate isochromenes in situ that participate in stereoselective allylation/spiroketalization sequence with 2-(1-hydroxyallyl)phenols. Meanwhile, 2-(1-hydroxyallyl)anilines were also compatible in this casc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 99 publications
0
7
0
2
Order By: Relevance
“…The asymmetric reaction resulted in a series of dibenzannulated [6,6]-spiroketals and [6,6]-spiroaminals 82 in 35-92% yields, 1.2 : 1->20 : 1 dr. and 88->99% ee (Scheme 33). 71 Many different substituents such as methyl, methoxy, t-butyl, ester, halo and thiazole groups on the phenyl ring of starting substrates could all tolerate this ternary catalytic system. All these results demonstrated a wide substrate scope for this asymmetric ternary catalytic methodology.…”
Section: Catalytic 6-endo-dig Oxocyclizationmentioning
confidence: 99%
“…The asymmetric reaction resulted in a series of dibenzannulated [6,6]-spiroketals and [6,6]-spiroaminals 82 in 35-92% yields, 1.2 : 1->20 : 1 dr. and 88->99% ee (Scheme 33). 71 Many different substituents such as methyl, methoxy, t-butyl, ester, halo and thiazole groups on the phenyl ring of starting substrates could all tolerate this ternary catalytic system. All these results demonstrated a wide substrate scope for this asymmetric ternary catalytic methodology.…”
Section: Catalytic 6-endo-dig Oxocyclizationmentioning
confidence: 99%
“…过渡金属 催化的偶极体及前体参与的不对称环加成反应近年来 发展得十分迅速, 逐渐成为构建手性螺环化合物的重要 策略 [30] . 2022 年, 邓卫平课题组 [31] 同年, 邓卫平课题组 [32]…”
Section: 邻羟基苄醇与活泼亚甲基类化合物的催化不 对称[4+2]环加成反应unclassified
“…Catalytic asymmetric addition reaction of o-hydroxybenzyl alcohols with enamines [32,40,44] . 所以, 很有必要探究邻羟基 苄醇参与催化不对称反应的反应性和立体选择性的理 论根源, 解释并推测邻羟基苄醇参与的催化不对称反应 的活化模式和可能的过渡态, 为邻羟基苄醇参与的新型 反应的设计与开发奠定理论基础; (5)虽然邻羟基苄醇参 与的催化不对称反应为合成结构多样的手性含氧杂环 化合物及芳基甲烷化合物提供了高效的方法, 但是目前 针对这些产物的应用性研究非常有限, 仅有一些研究工 作涉及到这些手性化合物在天然产物合成 [22,31] 、生物活…”
Section: 邻羟基苄醇参与的催化不对称[4+3]环加成反应unclassified
“…23,24 Recently, the Deng group also demonstrated that the exocyclic enol ethers were excellent synthons for the synthesis of chiral spiroketals via asymmetric [4 + 2] cycloaddition (Scheme 1b, path v). 25,26 On the other hand, 1,4-quinones are considered as useful building blocks for construction of oxygen-containing heterocyclic compounds, 27−31 and the related catalytic asymmetric applications in organic synthesis are thriving. 32−36 continuation of our interest in asymmetric transformations of 1,4-quinone, 37,38 we envisioned the possibility of a chiral Lewis-acid-promoted intermolecular cycloaddition of exocyclic enol ethers with 1,4-quinones to establish benzannulated spiroketals.…”
mentioning
confidence: 99%
“…Yeung and Tse innovatively developed an organocatalitic enantio- and diastereoselective domino halocyclization and spiroketalization of olefinic keto-acids with a halogen source through a dynamic–kinetic resolution process of the key lactol intermediate (path iv) . Our group reported an asymmetric cycloisomerization/[4 + 2] cyclization cascade reaction of keto esters with alkynyl alcohols or β-alkynyl ketones by employing a bimetallic relay catalytic system, wherein the key exocyclic enol ether intermediates were involved (path v). , Recently, the Deng group also demonstrated that the exocyclic enol ethers were excellent synthons for the synthesis of chiral spiroketals via asymmetric [4 + 2] cycloaddition (Scheme b, path v). , …”
mentioning
confidence: 99%